Elevated levels of apolipoprotein D predict poor outcome in patients with suspected or established coronary artery disease. (January 2022) - Annema, Wijtske; Gawinecka, Joanna; Muendlein, Axel; Saely, Christoph H.; Drexel, Heinz; von Eckardstein, Arnold
Abstract: Background and aims: Apolipoprotein D (apoD) is a lipocalin exerting neuroprotective effects. However, the relevance of apoD in respect to cardiovascular risk is largely unexplored. Therefore, this study aimed to evaluate the ability of apoD to predict future all-cause mortality, cardiovascular mortality, and cardiovascular events. Methods: Serum apoD levels were measured in a cohort of 531 Caucasian individuals who underwent coronary angiography (356 males, 175 females; mean age 65 ± 10 years). Fatal and non-fatal events were recorded over a median follow-up period of 5.8 years. Results: ApoD concentrations at baseline correlated significantly with age, presence of the metabolic syndrome, body mass index, lipoprotein levels, fasting glucose, and estimated glomerular filtration rate. Kaplan-Meier curve analyses by gender-stratified quartiles of apoD revealed that the cumulative incidence rates of mortality and cardiovascular events become higher with increasing apoD levels. The adjusted hazard ratios for participants in the highest quartile of apoD compared to those in the lowest quartile were 4.00 (95% confidence interval [CI] 1.49–10.74) for overall mortality, 5.47 (95% CI 1.20–25.00) for cardiovascular mortality, and 2.52 (95% CI 1.28–5.00) for cardiovascular events. Conclusions: High circulating levels of apoD are an indicator of poor prognosis in patients with suspected or established coronary artery disease. Graphical abstract: Image 1 Highlights: ApoD is a prognostic marker in patients with suspected or established coronary artery disease (CAD). High apoD levels are associated with an increased risk for mortality. High apoD levels are associated with an increased risk for cardiovascular events.